Carbon dioxide capture using a superhydrophobic ceramic hollow fibre membrane for gas-liquid contacting process - Abdulhameed, Mohammed Abdulmunem; Othman, Mohd Hafiz Dzarfan; Ismail, Ahmad Fauzi; Matsuura, Takeshi; Harun, Zawati; A. Rahman, Mukhlis; Puteh, Mohd Hafiz; Jaafar, Juhana; Rezaei, Masoud; Hubadillah, Siti Khadijah (ScienceDirect, 2018)
This work initiates the development of clean technology in carbon dioxide (CO2) capture using ceramic membrane inspired by gaseliquid contacting system. A low cost, high performance superhydrophobic kaolin-alumina hollow fibre membrane was prepared via phase inversion-based extrusion and sintering techniques, followed by a grafting with fluoroalkylsilane (FAS). The membrane was characterized by scanning electron microscopy (SEM), gas permeation test, contact angle, wetting resistance, X-ray photoemission spectroscopy (XPS), X-ray diffraction (XRD) and thermal gravimetric analysis (TGA). The fabricated membrane was highly porous, thus increasing the gas permeation rate. By surface modification, the membrane contact angle was increased from 0 to 142. In fact, wettability resistance of the membrane was also improved. The membrane was subsequently applied in membrane contactor for carbon dioxide (CO2) absorption. The CO2 absorption flux as high as 0.18 mol m2 s 1 was achieved at the liquid flow rate of 100 mL min1 which was far above the fluxes of some commercial and in-house made polymeric and ceramic membranes. In conclusion, the modified kaolin-alumina hollow fibre membrane with the superhydrophobic surface, high permeance, and absorption flux is suitable for CO2 postcombustion capture, due to its outstanding chemical and thermal stabilities